Stress and the impact on the outcome of medically assisted reproduction. (May 2020) - Geisler, Minna; Meaney, Sarah; Waterstone, John; O'Donoghue, Keelin
Abstract: Objectives: There is evidence to suggest that high perceived stress in early pregnancy is associated with increased rates of miscarriage. Our objective was to determine if psychological stressors have an impact on medically assisted reproduction (MAR) cycle outcomes including miscarriage rates. Study design: A survey-based study of women recruited prior to commencing MAR treatment and followed prospectively for treatment outcome (negative/positive pregnancy test, miscarriage) during the study period 2013–2015. The survey focused on perceived stress, emotional well-being, maternal social support and outlook. The women were asked to grade their responses according to a specified scale. Results: 320 women responded to the survey (response rate 64 %, 320/498). 290 (90 %, 290/320) women proceeded to MAR of which 58 % (n = 167/290) conceived. Analysis of stressful life events in the preceding 12 months, including job stress or serious financial problems did not reveal significance in terms of conception. A small number had experienced serious illness in the preceding 12 months which demonstrated significance in terms of not achieving pregnancy. Overall, there were high rates of emotional wellbeing, very high rates of maternal support and medium to low levels of perceived stress and this did not differ amongst those who conceived and failed to conceive. The data were further analysed according to livebirth and miscarriage (biochemical pregnancy and miscarriage). Analysis of stressful life events revealed a higher rate of miscarriage amongst those who reported a stressful/demanding job (p < 0.05). A number of women reported non-specified stressful life events and separation/divorce in higher numbers amongst the miscarriage group, reaching statistical significance, however the numbers are small thus limiting interpretation. Psychological factors had no impact on the risk of miscarriage amongst the group. Conclusion: This study suggests that stressors do not impact greatly on conception rates from MAR but may negatively impact on miscarriage rates. Job-related stress, in particular, is associated with higher risk of miscarriage. This suggests that there may be a role for stress management in early pregnancy.